1992
DOI: 10.1007/bf01954374
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate and oxygen uptake response to exercise in children with low peak exercise heart rate

Abstract: Normal children achieve the same increase of oxygen uptake (VO2) in response to exercise even though resting and submaximal exercise heart rates vary greatly as a function of age, body size and physical conditioning. To determine whether the VO2 response to exercise is altered when heart rate is significantly reduced by heart disease, we compared 78 children who achieved a peak exercise heart rate of less than or equal to 150 beats/min to 201 controls of similar body size and normal peak exercise heart rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…The reduced heart rate response contributes to the reduced VO 2max in these patients. However, low submaximal heart rates have little effect on submaximal VO 2 , which is usually normal, a finding consistent with a recent comparison of patients with markedly reduced maximal heart rates (ഛ150 beats/min) to patients with a normal heart rate response to exercise [75]. It should be noted that performance indices which are based on regressing heart rate on work rate, such as the W170 (power at a heart rate of 170 beats/min), tend to overestimate work capacity in the presence of a reduced heart rate response to exercise and should therefore not be used in tetralogy patients [10,52,91].…”
Section: Heart Rate Responsesupporting
confidence: 68%
“…The reduced heart rate response contributes to the reduced VO 2max in these patients. However, low submaximal heart rates have little effect on submaximal VO 2 , which is usually normal, a finding consistent with a recent comparison of patients with markedly reduced maximal heart rates (ഛ150 beats/min) to patients with a normal heart rate response to exercise [75]. It should be noted that performance indices which are based on regressing heart rate on work rate, such as the W170 (power at a heart rate of 170 beats/min), tend to overestimate work capacity in the presence of a reduced heart rate response to exercise and should therefore not be used in tetralogy patients [10,52,91].…”
Section: Heart Rate Responsesupporting
confidence: 68%
“…Although the sinus node artery and/or damage to specialized intraatrial conduction tracts have been implicated in the heart rate and arrhythmia issues [46], additional factors such as altered cardiovascular/pulmonary reflexes may well be involved considering that low maximal heart rates are also observed in adult heart disease [16] and after operations for other congenital heart lesions [45].…”
Section: Heart Rate Responsementioning
confidence: 99%
“…39 When data from earlier publications were compared with ours, values for HR reserve and VO 2peak were comparable. 7,27,28 …”
Section: Limitationsmentioning
confidence: 99%
“…A somewhat lower HR peak does not invalidate the exercise parameters obtained in a child. Schulze-Neck et al 28 found that VO 2peak /kg values were comparable in children who achieved a HR peak greater than 180 bpm compared with children with a HR peak lower than 180 bpm.…”
mentioning
confidence: 98%